Altered structure and function of adipose tissue in long-lived mice with growth hormone-related mutations. (3rd April 2017) - Darcy, Justin; McFadden, Samuel; Bartke, Andrzej
ABSTRACT: A major focus of biogerontology is elucidating the role(s) of the endocrine system in aging and the accumulation of age-related diseases. Endocrine control of mammalian longevity was first reported in Ames dwarf ( Prop1 df ) mice, which are long-lived due to a recessive Prop1 loss-of-function mutation resulting in deficiency of growth hormone (GH), thyroid-stimulating hormone, and prolactin. Following this report, several other GH-related mutants with altered longevity have been described including long-lived Snell dwarf and growth hormone receptor knockout mice, and short-lived GH overexpressing transgenic mice. One of the emerging areas of interest in these mutant mice is the role of adipose tissue in their altered healthspan and lifespan. Here, we provide an overview of the alterations in body composition of GH-related mutants, as well as the altered thermogenic potential of their brown adipose tissue and the altered cellular senescence and adipokine production of their white adipose tissue.